Konsep, Teori dan Praktik Obligasi Syariah - Fauzulhaq, Muhammad Fadlilah (Faculty of Shariah and Law, 2013)
One of the growing sharia finance instruments is sharia bond. Sharia bond is securities or certificate that contains the contract between funders (investors) with a given fund (the issuer). Sharia bond is supported by the Sharia Securities Act (SBSN) on April 9, 2008, so it can grow a new optimism for national Islamic banking and finance industry. SBSN Act paved the way for the issuance of sharia government and private bonds, in practice of Islamic bonds may use multiple inclusion models in the form of mudharabah, ijarah, and musyarakahDOI: 10.15408/aiq.v5i2.2124